Feasibility of the use of Kangaroo mother care in the transfer of preterm and low-birth-weight infants: a two-arm nonrandomized controlled cluster feasibility study of neonatal transport in Cape Coast, Ghana - Emmanuel Okai; Frankie Fair; Hilda Danquah Konadu; Eugene K M Darteh; Hora Soltani (BMC Pediatrics)
Abstract Background Despite progress made towards SDG 3, sub-Saharan Africa lags behind the rest of the world, accounting for over 50% of global neonatal deaths. The increased number of hospital births in the region has not reciprocated the reduction in neonatal mortality rates. Sick newborns face uncertain journeys from peripheral facilities to specialized centres arriving in suboptimal conditions, which impacts their outcomes, due partly to the scarcity of dedicated neonatal transport services. Methods This was a 2-arm nonrandomized controlled cluster study of preterm and low-birth-weight neonates transferred from eight peripheral sites to a tertiary neonatal unit via conventional methods or the KMC (August 2022–April 2023). Results A total of 77 (mother-baby pairs) were recruited, 34 in the KMC group and 43 in the conventional arm. Most (60%) were transported by taxis/private cars. Overall mortality was 20.8%. No untoward event was recorded for neonates transported by KMC, with marginally better temperatures on arrival. Although the observed differences were not statistically significant given that this was not the primary aim, the findings add to evidence that KMC transport may not be more life-threatening than the current practice of transporting newborns in the caregiver’s arms. KMC transport has the added advantage of ensuring non-separation of the small and sick child from its mother from birth and improved temperatures upon arrival. Conclusion KMC transport for preterm and Low birth weight infants using available transport in Sub-Saharan Africa is feasible. Local large-scale randomized trials are needed to gather more evidence for policy direction needed to inform a scale-up of this low-cost intervention. Trial registration ISRCTN98748162. Retrospectively registered 02.09.2024.